Petromyzon marinus (Petromyzontidae), an unusual host for helminth parasites in Western Europe - Gérard, Claudia; Verrez-Bagnis, Véronique; Jérôme, Marc; Lasne, Emilien (Diseases of Aquatic Organisms, 2015)
International audience The sea lamprey Petromyzon marinus, which is among the most phylogenetically ancient vertebrates, is a hematophagous ectoparasite that feeds on vertebrates and is considered vulnerable in Europe but is a pest in the North American Great Lakes. We conducted a literature review of helminth parasites of P. marinus and investigated postmetamorphic lampreys sampled in rivers and northeast Atlantic coastal waters (western France) during spawning migration. Based on the literature review, 16 helminth taxa have been recorded in P. marinus, among them 14 in North America but only 2 in Europe, with no species in common between these areas. Specific parasites are lacking, and helminth parasites recorded in P. marinus are mostly opportunistic and are trophically transmitted to fish hosts with both extremely low prevalence and mean intensity. Thus, P. marinus seems an unusual host that is probably infected through accidental ingestion of parasites by microphagous larvae (ammocoetes) and/or hematophagous postmetamorphs. Our field study supports this hypothesis, since only a single third-stage larva of Anisakis simplex sensu stricto was found in 2 postmetamorphic P. marinus among the 115 individuals dissected. This opportunistic, trophically transmitted, and cosmopolitan nematode species has never been recorded in North American sea lampreys and only once in Galician rivers (southern Europe). Infestation pathways of P. marinus by A. simplex are proposed vis-à-vis the feeding strategy of postmetamorphs and fish host species which potentially harbor anisakid larvae in their musculature. More generally, the complexity of biotic interactions is discussed considering P. marinus both as a host for helminth parasites and as a parasite for hosts such as fish and mammals, which are also potential predators of sea lamprey.